PENEGAKAN HUKUM LINGKUNGAN PENGELOLAAN SAMPAH DI KABUPATEN BOYOLALI DALAM RANGKA MEWUJUDKAN PRINSIP GOOD ENVIRONMENTAL GOVERNANCE - Purwanto Purwanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
Enforcement of Environmental Law on waste management is an unresolved problem, especially in Boyolali Regency in realizing Boyolali Boyolali Green City. This study aims to determine the existence of Human Resources in supporting the Law Enforcement of Waste Management in Boyolali Regency. This research is a normative legal research with a statutory approach. Data were collected by literature study and then analyzed qualitatively. The Boyolali Regency Environmental Service does not yet have a functional position to carry out special duties and functions in environmental management such as the RegionalEnvironmental Supervisory Officer (PPLHD) and PNS Investigators for environmental affairs. Supervision in the environmental field is attached to the tasks of the Licensing, Guidance, and Environmental Compliance Sector. The existing regulations in Boyolali Regency, namely the Boyolali Regency Regulation Number 13 of 2013 concerning Waste Management have not been followed up with the Regent's Regulation so that they have not been able to accommodate as a legal basis in their implementation, and have not been able to reach the implementation level of legal action.